Experimental study of camptothecin combined with drug-eluting bead transarterial chemoembolization in the rabbit VX2 liver tumor model - Meng, Fanguang; Li, Yuyao; Liu, Qian; Sun, Liwei; Wang, Hankang; Li, Xiaodong; Li, Guijie; Chen, Feng (Frontiers in Oncology, 2022)
Drug-eluting bead transarterial chemoembolization (DEB-TACE) has been widely used in the treatment of liver cancer; however, the utilization rate of chemotherapeutic drugs after embolization is low. Chemotherapy resistance mediated by high nuclear factor E2-related factor 2 (NRF2) expression limits DEB-TACE efficacy. Camptothecin (CPT), an NRF2 inhibitor, exerts chemosensitizing effects. We designed a controlled experiment to determine the efficacy and feasibility of DEB-TACE combined with CPT for the treatment of rabbit VX2 hepatoma. DEB-TACE activated NRF2 expression in the tumor region. NRF2 activation could be inhibited by the combined use of CPT. After DEB-TACE alone, the tumor necrosis was incomplete, there were still highly active tumor residues, and the apparent diffusion coefficient (ADC) value, which was negatively correlated with tumor activity observed by magnetic resonance imaging, remained low. After DEB-TACE combined with CPT, the relative necrosis of the tumor was more complete, the ADC value was higher, and the ADC change was greater. The single application of CPT did not result in evident liver function and physical burden to the rabbits. The combined use of CPT and DEB-TACE did not significantly increase DEB-TACE imaging of liver function and body. In conclusion, CPT can also inhibit high NRF2 expression after DEB-TACE treatment. Combining CPT with DEB-TACE can improve the sensitivity of DEB-TACE in the treatment of VX2 tumors, improve the therapeutic effect, and has no evident toxic and side effects. This study explored the methods for enhancing the efficacy of DEB-TACE in liver cancer from a new perspective and performed model experiments, which provided a theoretical basis for future clinical treatment.